Using focus groups to plan culturally acceptable primary cervical cancer screening in Grenada, West Indies - Calisha Hyacinth-Purcell; Jeannine Sylvester-Gill; Edwin Sperr; Jane McPherson; Amy Baldwin (Pan American Health Organization, 2023)
Objective. To document Grenadian women's knowledge about cervical cancer and human papillomavirus (HPV) infection, as well as their attitudes towards primary cervical cancer screening methods. Methods. In this qualitative study, we used focus groups in Grenada to gather information concerning women's knowledge about, attitudes towards and perceptions of screening for cervical cancer and general knowledge about HPV. Ten focus groups comprising 73 participants representing 5 of the 6 parishes in Grenada were conducted with women aged 19-59. Participants were asked about pelvic exams, Pap smears, HPV, reasons for seeking or avoiding cervical cancer screening and how different modalities of testing might affect their decision-making. Responses were then coded and organized into common themes. Results. While many respondents had heard of HPV, far fewer knew about its causative role in cervical cancer, how to prevent HPV infection or testing for the high-risk HPV types that cause almost all cases of cervical cancer. Many participants were aware that cervical cancer screening was beneficial, but numerous barriers to obtaining that screening were noted, including concerns about privacy and stigma, potential discomfort, and the cost and inconvenience involved. Conclusions. Our findings have implications for future cervical cancer screening efforts in Grenada. Central to these efforts should be a focus on educating Grenadians about the role of HPV infection in cervical cancer and the importance of early detection through screening. In addition, addressing issues of stigma and privacy are key to eliminating cervical cancer in Grenada.